Imperfect competition with costly disposal - Severin Lenhard (University of Bern, Department of Economics, 2021)
This paper studies the disposal costs' effect on consumer surplus and firms' profits. The costlier disposal, the less is disposed of, firms' competition for market shares increases, thereby benefiting consumers. Yet firms decrease their production to mitigate costs, affecting consumer surplus negatively. We present a model with ex ante homogeneous firms producing inventories either early at low cost and with little information about demand, or later with more information yet at higher costs. Unsold products are disposed of. In equilibrium, firms may be asymmetric. Disposal goes down with costs but so do inventories. In our set-up, the negative effect on the trade volume dominates decreasing consumer surplus and firms' profits. We show, however, that low disposal costs substitute information about demand. Increasing disposal costs improve a firm's information advantage and may increase its profits.
Keywords: D43; L11; L13; L50; 330; Disposal; Inventory; Uncertain Demand; Market Structure